Estimates for a Group of Deviations in Generalized Hölder Metric - Lasuriya, R. A. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We present order relations for a group of deviations of a function f(·) ∈ H ω in terms of partial Fourier sums of this function in a generalized Hölder metric defined in a generalized Hölder space H ω* ⊃ H ω.